ABILITY TO MANAGE THE KNOWLEDGE AND COMPETITIVE ADVANTAGE: Applied to ICT Companies in the Gaza Strip affiliated with the Palestinian Information Systems Association (PITA) - Mahahy, Rima Mustafa (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aims to determine the impact of knowledge management on the competitive advantage of the sector companies by clarifying the impact of different components of ability to manage the knowledge and competitive advantage by applying to the ICT companies in the Gaza Strip of the Palestinian Information Technology Association ( PITA). The research problem was the main question: What is the impact of knowledge management on the competitive advantage of sector companies?. The main objective of the research was to identify the impact of knowledge management on the competitive advantage of sector companies. The researcher used the analytical descriptive approach. To achieve the objectives of the study, an electronic questionnaire made up of two parts: The first part includes the data of the study sample. The second part includes 9 main themes. The data were processed through the application of the Statistical Package for Social Sciences(SPSS). The researcher used the analytical descriptive approach, which tries to describe, assess and interpret the reality of "the impact of knowledge management on the competitive advantage of the sector companies. The study community is composed of officials at various administrative levels (top, middle and low) in ICT companies in the Gaza Strip(PITA), The researcher used an electronic questionnaire was sent to the companies through the e-mail of these companies made up of two parts: The first part includes the data of the study. One of the most important findings of the researcher There is a statistically significant impact of the variable capacity of the social infrastructure to knowledge management (organizational structure, organizational culture, individuals) on the competitive advantage. There is a significant impact of the variable capacity of knowledge management processes (acquisition, conversion, application, protection) on the competitive advantage of the companies subject of study. There is a statistically significant impact of the ability of the IT infrastructure to knowledge management on competitive advantage the most important recommendations recommended by the study. The focus was on the top management of all companies wishing to maintain their competitive advantage adopting the method of knowledge management building Administrations or departments specializing in this field have an active player position in the organizational structure of the company, The need to pay attention in the knowledge; held by the employees and motivate them to retain knowledge. The need for the company to pay attention to knowledge in its environment. Moreover, the need to pay attention to the rules of knowledge and apply these rules to achieve a competitive advantage.
Keywords: knowledge management; knowledge management ability; competitive advantage